Positive benefit of postnatal treatment in congenital toxoplasmosis (2006)
We read the editorial of Gilbert and Desateux.1 In their analysis, they take into account some newborn screening programmes for congenital toxoplasmosis in developing countries such as Brazil and Mexico, with reported rates of up to a maximum of 20 cases/10 000 live births; however, they did not mention our recent report that found a prevalence of 0.5% in a reference hospital in Colombia.2 This study found one child who died 1 week after birth. As we had information only on the frequency of deaths in a reference hospital, we carried out a study in a representative sample of all newborns from Quindio and found nearly the same prevalence: 0.6%